Imagined futures of retail and consumption - Shahriar, Hossain ; 0000-0001-6862-7617; Wulff, Gabriella (International Review of Retail Distribution & Consumer Research, 2026)
Retail and consumption stand at a precipice, tethered to the urgency of the planetary crisis and propelled by the accelerating force of digital transformation. At this crossroads, we introduce imagined retail and consumption futures as the organising concept for this special issue on the Future of Retail and Consumption. Drawing on Jens Beckert’s theory of fictional expectations, we argue that the future of retail and consumption is a contested terrain of competing narratives that, by motivating present action, partially bring themselves into being and obscure others that go unfunded and unbuilt. We articulate three features of imagined futures (narrativity, performativity, and contestation) and four tensions that structure how they are negotiated in scholarship and in practice: accumulation (circular economy versus growth capitalism), accountability (consumer responsibilisation versus collective provisioning), sovereignty (consumer agency versus platform governance), and tangibility (physical circulation versus digital dematerialisation). The seven contributions to the special issue are illustrated through this framework, making plausible a future in which sustainability is approached as a systemic property of well-designed retail environments, irreducible to the cumulative outcome of individually enlightened choices. We close with a research agenda that considers how certain retail and consumption futures become plausible, funded, designed, and normalised, while others remain peripheral, underfunded, or difficult to imagine.
Keywords: Future of retail and consumption; Fictional expectations; Imagined futures; Sustainability; Digitalisation